Surgical correction and histopathological characterisation ofvaginal hyperplasia in a Labrador Retriever dog - Nayana Devarajan,; Simon, Shibu; Becha B, Bibin; R S, Abhilash; Devi , S S; Reddy, Y V Pridhvidhar; T P, Ananthapadmanabhan; Alaka S, uresh (The Indian Journal of Animal Reproduction, 2024)
Canine vaginal hyperplasia is one of the frequently encountered vaginal pathologies, often unnoticed too. The condition is mostly observed during the follicular phase of the oestrous cycle in bitches. Clinically the condition is mostly observed during the follicular phase of the oestrous cycle in bitches. Clinically the condition is established as a swollen mass which could vary in size and shape. A nulliparous intact female labrador retriever, aged two years, was presented to the university veterinary hospital, Kokkalai, with the complaint of a mass protruding from the vulva for the past two weeks. Histopathology of the protruded vaginal mass revealed keratinised and hyperplastic vaginal epithelium with focal areas of mild spongiosis. Subsequently, the condition was diagnosed as vaginal hyperplasia Type III and the condition was managed with surgical circumferential excision under general anaesthesia. No recurrence was observed on the succeeding oestrous cycle.
Keywords: Ford interlocking suture pattern; Surgical excision; Vaginal hyperplasia